Counseling For Early Childhood In An Effort To Increase Learning Independence - Eli Ermawati; Warto Warto (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
In increasing children's learning independence at an early age, one of them is by providing guidance and counseling services that start as early as possible. Counseling guidance can be defined as a process of providing assistance to individuals and groups in terms of decision making and behavior change and helping individuals solve the problems they face. The purpose of counseling guidance services provided to early childhood is so that children can develop their skills both academically and non-academically and provide opportunities for active and preventive learning so that children can increase success in their learning. This study aims to determine the independence of learning in children at Al-Hayat Kindergarten with the Teacher. This research is descriptive qualitative research, where the data produced is in the form of descriptions and expressions of words from the subject. While this research method is in the form of interviews, observation and documentation used by researchers at Al-Hayat Kindergarten during KKN, with the aim of obtaining appropriate data about learning independence in students. Today the results of the study can be concluded that there are still many students who are still awaited by their parents and the level of independence in children who can be said to be in a less independent condition so that it is necessary to hold counseling guidance services to increase learning independence in students. This can be done by teachers by providing counseling guidance services to early childhood and parents so that children are able to develop their learning independence.